2018
DOI: 10.1177/0885066618758246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Implementing an Intensivist Model With Nighttime In-Hospital Nocturnist and Effect on ICU Outcomes

Abstract: Implementing an intensivist service with nighttime nocturnist staffing in a high-intensity large teaching hospital is feasible and improved ICU outcomes in a sustained manner that persisted after the initial implementation phase. The model resulted in reduced and sustained observed-to-predicted length of ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(47 reference statements)
0
6
1
Order By: Relevance
“…This lead to the suggestion that 24 × 7 intensivist staffing models may not be an effective use of intensivist resources in units with high-intensity staffing models (16,17). Interestingly, however, in another recent study, implementation of nighttime coverage with in-house nonintensivist ("nocturnist") physicians in a unit with a high-intensity staffing model did result in significant decreases in ICU length of stay (18). Independent of the coverage model employed to meet 24 × 7 demands in the ICU, intensivist-led multidisciplinary team models of ICU care are associated with decreased mortality risk for critically ill and injured patients (1,19).…”
Section: Intensivist-led Care In the Icumentioning
confidence: 99%
“…This lead to the suggestion that 24 × 7 intensivist staffing models may not be an effective use of intensivist resources in units with high-intensity staffing models (16,17). Interestingly, however, in another recent study, implementation of nighttime coverage with in-house nonintensivist ("nocturnist") physicians in a unit with a high-intensity staffing model did result in significant decreases in ICU length of stay (18). Independent of the coverage model employed to meet 24 × 7 demands in the ICU, intensivist-led multidisciplinary team models of ICU care are associated with decreased mortality risk for critically ill and injured patients (1,19).…”
Section: Intensivist-led Care In the Icumentioning
confidence: 99%
“…Analyses of patient-to-provider ratios have shown mixed results with some demonstrating a deleterious mortality effect of higher ratios (6, 7) but others suggesting no association (8). Mandatory involvement of trained intensivists in ICU patient care, often referred to as a "closed" ICU model, has been associated with improved patient outcomes in multiple studies at single academic medical centers (9)(10)(11)(12)(13)(14)(15); however, large cohort studies of multiple academic and community-based ICUs have not been able to replicate this finding (16,17). One factor contributing to this inconsistency could be differences of effects between academic and community sites.…”
mentioning
confidence: 99%
“…
N octurnists (overnight hospitalists) have been widely implemented in teaching hospitals in the United States in an effort to meet Accreditation Council for Graduate Medical Education workload standards, 1 improve overnight supervision and enhance the quality of patient care. [2][3][4][5][6][7][8] Recent data indicate that about 50% of US teaching hospitals have nocturnists. 9 Several single-centre surveys from the US suggest that nocturnist programs improve perceived quality of care, increase resident satisfaction with overnight supervision and may enhance efficiency.
…”
mentioning
confidence: 99%
“…9 Several single-centre surveys from the US suggest that nocturnist programs improve perceived quality of care, increase resident satisfaction with overnight supervision and may enhance efficiency. 3,7 However, studies have not shown reductions in hospital length of stay or rates of mortality or hospital readmission. 2 Canadian teaching hospitals have been slow to implement nocturnists.…”
mentioning
confidence: 99%